Sensitized Photocatalytic CO2 Reduction With Earth Abundant 3d Metal Complexes Possessing Dipicolyl-Triazacyclononane Derivatives - Obermeier, Martin; Beckmann, Fabian; Schaer, Raoul S.; Wenger, Oliver S.; Schwalbe, Matthias (Frontiers in Chemistry, 2021)
Complexes based on nitrogen and sulfur containing ligands involving 3d metal centers are known for the electrocatalytic reduction of CO2. However, photocatalytical activation has rarely been investigated. We herein present results on the light-driven CO2 reduction using either Ir(dFppy)3 [Ir, dFppy = 2-(4,6-difluorophenyl)pyridine] or [Cu(xant)(bcp)]+, (Cu, xant = xantphos, bcp = bathocuproine) as photosensitizer in combination with TEA (triethylamine) as sacrificial electron donor. The 3d metal catalysts have either dptacn (dipicolyl-triazacyclononane, LN3) or dpdatcn (dipicolyl-diazathiocyclononane, LN2S) as ligand framework and Fe3+, Co3+ or Ni2+ as central metal ion. It turned out that the choice of ligand, metal center and solvent composition influences the selectivity for product formation, which means that the gaseous reduction products can be solely CO or H2 or a mixture of both. The ratio between these two products can be controlled by the right choice of reaction conditions. With using Cu as photosensitizer, we could introduce an intermolecular system that is based solely on 3d metal compounds being able to reduce CO2.